If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying ln(x + -8) + -1ln(x + 2) = ln(11) Reorder the terms: ln(-8 + x) + -1ln(x + 2) = ln(11) (-8 * ln + x * ln) + -1ln(x + 2) = ln(11) (-8ln + lnx) + -1ln(x + 2) = ln(11) Reorder the terms: -8ln + lnx + -1ln(2 + x) = ln(11) -8ln + lnx + (2 * -1ln + x * -1ln) = ln(11) -8ln + lnx + (-2ln + -1lnx) = ln(11) Reorder the terms: -8ln + -2ln + lnx + -1lnx = ln(11) Combine like terms: -8ln + -2ln = -10ln -10ln + lnx + -1lnx = ln(11) Combine like terms: lnx + -1lnx = 0 -10ln + 0 = ln(11) -10ln = ln(11) Reorder the terms for easier multiplication: -10ln = 11ln Solving -10ln = 11ln Solving for variable 'l'. Move all terms containing l to the left, all other terms to the right. Add '-11ln' to each side of the equation. -10ln + -11ln = 11ln + -11ln Combine like terms: -10ln + -11ln = -21ln -21ln = 11ln + -11ln Combine like terms: 11ln + -11ln = 0 -21ln = 0 Divide each side by '-21'. ln = 0 Simplifying ln = 0 The solution to this equation could not be determined.
| (3x+2)(x+2)=4 | | 32.4=4p | | e^4-5x=3 | | 25x+24x+5=180 | | m/2.6=3.5 | | 32n=99.2 | | 6z+2=-6z+50 | | 5=s/3.7 | | 8(4+2x)=4(3-5x)+4x | | n/2.1=12 | | 6(x+3)=6x | | abs(2x^2-5)+6=7 | | 7y+3=6x+2 | | s^5+4s^4+4s^3=0 | | p*3.4=7.48 | | -138=-2+3(-6x+14) | | e^4x-e=0 | | 8y+4=9y | | x/8=5.6 | | 3x-5(3x-12)=156 | | 10×1/8= | | 10×1/8 | | 8sin(2x)-sin(4x)=0 | | ln(9x)+ln(4x)=5 | | 67.3=3.2q | | 188=4x+5(2x+4) | | y=3/2x-4/9 | | 4x-15x=66 | | 160=3x+7(4x-17) | | 3(3x+5)=36 | | 6x+2(6x-7)=76 | | 3a-2=5a |